STRATEGIC PLANNING OF CONTAINER VILLAGES FOR THE RENTAL COMPANY IN INDONESIA - Hasan Al Mufarrid Drihim; Tanti Yanuar Rahmad; Rhian Indradewa; Muhammad Dhafi Iskandar (Syntax Corporation Indonesia, 2023)
With industrial development and population growth in Indonesia, the demand for residential facilities such as container villages is increasing. Container village is a housing concept that uses used containers as residential units. This research aims to identify appropriate strategies for container rental companies in Indonesia to develop and utilize container villages. This research uses qualitative research methods. The data collection technique was carried out with a literature review. The data that has been collected is then analyzed through the stages of data reduction, data presentation and conclusion drawing. The results showed that in the formulation situation for strategic planning, the first step that must be done is to make the company's vision and mission first. We have done this in chapter 1 (one). The second step is to determine the objectives. For the purpose of researchers dividing into 3 (three) parts, namely short-term goals, medium-term goals and long-term goals. In the strategic planning process of PT Nahe Unggul Lestari starting from gather inputs, SWOT Analysis, Review Inputs, Strategic Matrix, Define Strategies and Final Reviews.